Respon Siswa Terhadap Pembelajaran Daring Materi Teks Eksplanasi Melalui Metode Inkuiri Berbantuan Media Sosial Instagram - Riani Rahmawati; Wikanengsih Wikanengsih; Via Nugraha (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
One of the learning solutions during the Covid-19 outbreak is to do online learning. However, when online learning is implemented, of course there are many obstacles experienced by teachers or students. In practice, teachers must be able to determine the right methods and media during the online learning process. This study aims to determine student responses to online learning of explanatory text material through the Instagram social media assisted inquiry method. The method in this study uses a qualitative descriptive method by distributing questionnaires to class XI students at SMK PGRI 2 Cimahi, totaling 30 students. Online learning is done through the Google Meet application. Results Student responses to online learning explanatory text material through the inquiry method assisted by social media Instagram, namely students gave a positive response with an average response result of 83.7% are in the High category.